Functional and speciality beverage technology - Paquin, Paul (Woodhead Publishing in food science, technology, and nutrition, 2009)
Reviews the key ingredients, formulation technology, and health effects of functional and specialty beverages. This book covers ingredients such as stabilizers and sweeteners, and explores formulation issues such as fortification technology and methods to extend shelf-life